Intra- and inter-annual variability in dynamic discharge from the Academy of Sciences Ice Cap, Severnaya Zemlya, Russian Arctic, and its role in modulating mass balance. Issue 253 (28th August 2019) - Sánchez-Gámez, Pablo; Navarro, Francisco J.; Benham, Toby J.; Glazovsky, Andrey F.; Bassford, Robin P.; Dowdeswell, Julian A.
Abstract: We determined ice velocities for the Academy of Sciences Ice Cap, Severnaya Zemlya, Russian Arctic, during November 2016–November 2017, by feature-tracking 54 pairs of Sentinel-1 synthetic-aperture radar images. Seasonal velocity variations with amplitudes up to 10% of the yearly-averaged velocity were observed. Shorter-term (<15 d) intra-annual velocity variations had average and maximum deviations from the annual mean of up to 16 and 32%, respectively. This indicates the errors that could be incurred if ice discharge values determined from a single pair of images were extrapolated to the whole year. Average ice discharge for 2016–2017 was 1.93 ± 0.12 Gt a −1 . The difference from an estimate of ~ 1.4 Gt a −1 for 2003–2009 was attributed to the initiation of ice stream flow in Basin BC. The total geodetic mass balance over 2012–2016 was − 1.72 ± 0.67 Gt a −1 (− 0.31 ± 0.12 m w.e. a −1 ). The climatic mass balance was not significantly different from zero, at 0.21 ± 0.68 Gt a −1 (0.04 ± 0.12 m w.e. a −1 ), and has remained near zero at decadal-scale for the last four decades. Therefore, the total mass balance has been controlled largely by variations in ice discharge, whose long-term changes do not appear to have responded to environmental changes but to the intrinsic characteristics of the ice cap governing tidewater glacier dynamics.